2016
DOI: 10.1097/pec.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Caretakers' Perspectives on Return Pediatric Emergency Department Visits

Abstract: Several of the reasons parents identify for return visits are within the locus of control of the ED, and several could be addressed by improving regional health care coordination. Surveys based on these themes will quantitate the reasons for return visits and prioritize future strategies to address the perceived need for return visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 15 publications
5
41
0
Order By: Relevance
“…For example, caregiver's age, marital status and presence/age of other children were not associated with revisits in five studies 33 42–44 55. In contrast, other studies concluded that language spoken at home or single caregivers were associated with revisits 9 12 28 36 40 50 51 64. Next, we found conflicting evidence for the association between lower socioeconomic status and revisits 27 28 30 33 37 40 42 45…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…For example, caregiver's age, marital status and presence/age of other children were not associated with revisits in five studies 33 42–44 55. In contrast, other studies concluded that language spoken at home or single caregivers were associated with revisits 9 12 28 36 40 50 51 64. Next, we found conflicting evidence for the association between lower socioeconomic status and revisits 27 28 30 33 37 40 42 45…”
Section: Resultsmentioning
confidence: 90%
“…Strong evidence was found for the association between revisits and seizures or other nervous system diseases 27 37 39. Lastly, strong association was found between progression/persistence of symptoms and revisits 9 13 36 38 39 44 48 51–56…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations